Effects of dose response and 5 weeks of exercise on abdominal circumference and BMI in obese women - Siti Baitul Mukarromah; Septian Bagas Panji Kurniaziz; Nanang Indardi; Mohammad Arif Ali; Sugiarto; Sangheon Park (Journal Sport Area, 2023)
Being overweight, which results in a large belly circumference, is often overlooked, despite the fact that belly fat accumulation can endanger health. The purpose of this study was to determine the effect of changes in abdominal circumference and BMI after giving tabata training for 16 meetings. This study is a quasi-experiment that employs a one-group pre-test post-test group design with a population of all Powerfit Daru members and a total sample of 15 using a purposive sampling technique with sample criteria of having an abdominal circumference > 80 cm, being 25-40 years old, and being obese. The obtained data were processed using IBM SPSS version 26 and the paired T-test. The results showed that the average decrease in pre-test and post-test abdominal circumference was (94.86 8.79; 90.46 8.85) with a P value of 0.005 0.05. The results showed that the average change in BMI was 30.51 2.18; 29.96 2.65, with a P value of 0.418 > 0.05. The average decrease in abdominal circumference was -4.4 cm, and the BMI was -0.54 kg/m2. The conclusion of this study was that there was a significant decrease in changes in abdominal circumference with tabata exercise for 5 weeks of treatment but no significant decrease in BMI.